Tractates Bava Qamma, Bava Mesi'a, and Bava Batra - Guggenheimer, Heinrich W. (Studia Judaica, 2008)
The present volume is the eleventh in the series of the Jerusalem Talmud, the first in a three volume edition, translation, and commentary of the Fourth Order Neziqin. The thirty chapters of Neziqin that deal with most aspects of Civil Law are usually divided into three parts, or "gates", known as the First Gate, Bava qamma, the Middle Gate, Bava mesi'a, and the Last Gate, Bava batra. In contrast to the Babylonian Talmud, the treatment in the Jerusalem Talmud is fragmentary. The reason for this is a matter of controversy, discussed in the Introduction to the Tractate.